A Mixed Learning Approach in Mechatronics Education - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2011)
This study aims to investigate the effect of a Web-based mixed learning approach model on mechatronics education. The model combines different perception methods such as reading, listening, and speaking and practice methods developed in accordance with the vocational background of students enrolled in the course Electromechanical Systems in mechatronics education. For this purpose, the effectiveness of the model recommended for mechatronics education was investigated on a working group consisting of 32 sophomore students in the 2008-2009 Spring semester in the Mechatronics Department of the Faculty of Technical Education, Marmara University, Istanbul, Turkey. The 12-week-long Electromechanical Systems course is given each semester and covers the topics of mechatronics, electric principles, electrostatics, magnetism and principles, control components, control and power circuits, industrial electronics, and direct and alternating current motors. The text, pictures, and images for the Web-supported education materials used in the study were developed using Adobe Presenter and Adobe Captivate software. In addition, Adobe Flash was used to provide the interactivity between the students and the training content, and 3dsMax software was used for 3-D simulations. Finally, Adobe Connect Professional software was used as a learning management system. During this process, expert opinion in the field of educational sciences, instructional technologies, and electromechanical systems was consulted. The efficiency of the model recommended for mechatronics education was evaluated by using data collection forms and the results of interviews with the students.
Keywords: Learning; mechatronics education; Web-based mixed education; PERSPECTIVES